Photodynamic therapy mediates innate immune responses via fibroblast-macrophage interactions - Zulaziz, Natasha; Azhim, Azran; Himeno, Naomi; Tanaka, Masato; Satoh, Yasushi; Kinoshita, Manabu; Miyazaki, Hiromi; Saitoh, Daizoh; Shinomiya, Nariyoshi; Morimoto, Y. (Springer Japan, 2015)
Antibacterial photodynamic therapy (PDT) has come to attract attention as an alternative therapy for drug-resistant bacteria. Recent reports revealed that antibacterial PDT induces innate immune response and stimulates abundant cytokine secretion as a part of inflammatory responses. However, the underlying mechanism how antibacterial PDT interacts with immune cells responsible for cytokine secretion has not been well outlined. In this study, we aimed to clarify the difference in gene expression and cytokine secretion between combined culture of fibroblasts and macrophages and their independent cultures. SCRC-1008, mouse fibroblast cell line and J774, mouse macrophage-like cell line were co-cultured and PDT treatments with different parameters were carried out. After various incubation periods (1-24 h), cells and culture medium were collected, and mRNA and protein levels for cytokines were measured using real-time PCR and ELISA, respectively. Our results showed that fibroblasts and macrophages interact with each other to mediate the immune response. We propose that fibroblasts initially respond to PDT by expressing Hspa1b, which regulates the NF-κB pathway via Tlr2 and Tlr4. Activation of the NF-κB pathway then results in an enhanced secretion of pro-inflammatory cytokines (TNF-α, IL-6 and IL-1β) and neutrophil chemoattractant MIP-2 and KC from macrophages.